Habitar un cuento, habitar una lengua - Refugio Chávez Ramírez (Recherches)
Stories and tales are elements of escape and reverie, but they are also excellent instruments for perfecting language and grasping concepts that are more abstract. They acquire, thus, a meta-competence character (they promote the student’s ability of learning to learn). This text briefly presents how tales, when used in language teaching, guarantee multiple advantages. This essay presents the results of the ARTLINGO workshop organized at the University of Strasbourg with students of Spanish.